The Effect of the Change of Schemas on Recall - Lê, Phước Thục Nhi (H. : ĐHQGHN, 2017)
The aim of this study is to examine whether the change of schema would affect the process of encoding and retrieval. This experiment is a modification of Anderson and Pichert’s study (1977). The independent variable (IV) in the experiment was the two different schemas used in the study (Geography student or tourist) and the dependent variable (DV) was the extent to which the participants could recall the story, specifically the number of words in this case. The results suggested that a change in schema of the same story would improve recall, as found by Anderson and Pichert. The Mann Whitney U test indicated that the null hypothesis was accepted